Legal Examination of Corruption on Social Assistance in State Officers in State during Emergencies / National Disasters - Eva Yunita Siregar; Sriono Sriono; Muhammad Yusuf Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Abuse often occurs among politicians and state officials or officials who have authority or power over governance. Such misuse is like bribery for Social Funding, namely by receiving a certain amount of money to enrich oneself and fulfill all needs as suspected by the Corruption Eradication Commission to the Minister of Social Affairs of the Republic of Indonesia in 2020. The acts of corruption are committed when the state is in an emergency (national disaster) will certainly have an impact on the types of lawsuits. Provisions regarding national disasters as determined by the State. This study aims to analyze from a legal point of view criminal acts in the form of corruption in covid-19 social assistance funds. The method used in this research is normative juridical. Juridical normative is a method using secondary data in the form of library materials and statutory approaches (Statute Approach) and an approach to cases related to the author's title (Case Approach). The results showed that an act of corruption committed by a government official could be punished by imprisonment, but if the act of corruption was committed in certain circumstances (emergency/disaster) then the perpetrator could be sentenced to death.